Determination of lead in spiked seawater samples by electrothermal atomic absorption spectrometry using chemical modifiers - Dogan, Canan Ekinci; Ortner, Hugo Manfred (TAYLOR & FRANCIS INC, 2008)
The determination of lead in spiked sodium chloride solution with 3.4% salinity and natural sea-water samples by electrothermal atomic absorption spectrometry (ETAAS) with Zeeman-effect background correction was investigated using neodymium, samarium, and erbium salts as modifiers with the addition of citric acid (CA) as a reducing agent. In order to demonstrate the high potential of rare earth metals in combination with citric acid, optimum pyrolysis temperature, atomization temperature, and optimum masses of neodymium, samarium, and erbium were found for the determination of lead. These modifiers were used for the determination of lead in sodium chloride solution with 3.4% salinity and in natural sea water samples by means of the calibration graphs prepared with pure analyte solutions. The detection limits for lead spiked sample matrices were calculated with the 2 sigma criterion between 2.0 to 2.1 ng mL(-1) for neodymium and citric acid, between 5.3 to 7.4 ng mL(-1) for samarium and citric acid, and between 1.7 to 2.1 ng mL(-1) for erbium and citric acid and for a sample volume of 10 mu L. The recoveries for lead spiked sea water samples were 97-102%, with neodymium and citric acid modifier and erbium and citric acid modifier. They were only 66-68% without modifier.
Keywords: electrothermal atomic absorption spectrometry; lead; rare earth; modifier systems; citric acid; sea water samples; MAGNESIUM-NITRATE MODIFIER; SEA-WATER SAMPLES; GRAPHITE-FURNACE; ASCORBIC-ACID; PALLADIUM NITRATE; OXALIC-ACID; INDIUM; BISMUTH; INTERFERENCE; ELIMINATION; Chemistry; Instruments & Instrumentation